The Effects of the Jigsaw Type Cooperative Learning Model and Self-Efficacy on Elementary School Students’ Scientific Literacy Skills - Afifah, Adyati Nur; Darmiany; Ida Ermiana (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Science education at the elementary school level plays a crucial role in establishing students’ foundations for critical thinking and problem-solving skills, particularly in the context of 21st-century learning. This study aimed to examine the effects of the Jigsaw-type Cooperative Learning model and self-efficacy on elementary school students’ scientific literacy skills. A quantitative approach was employed using a pre-experimental one-group pretest–posttest design. The population consisted of all fourth-grade students at SDN 26 Mataram, with a purposive sampling technique applied. Research instruments included a self-efficacy questionnaire and a scientific literacy test. Data were analyzed using the Kolmogorov–Smirnov and Shapiro–Wilk normality tests, as well as a paired-sample t-test. The results revealed a significant increase in scientific literacy scores by 15.25 points following the implementation of the Jigsaw learning model. This improvement was accompanied by enhanced student self-efficacy, which fostered active engagement and responsibility in the learning process. The study concludes that the Jigsaw-type Cooperative Learning model is effective in improving both scientific literacy and self-efficacy among elementary school students, offering an active learning alternative aligned with the demands of modern curricula.